The Emerging Role of Osteocytes in Cancer in Bone. (27th February 2019) - Atkinson, Emily G; Delgado‐Calle, Jesús
ABSTRACT: Advances in the last decade have established the osteocyte, the most abundant cell in bone, as a dynamic and multifunctional cell capable of controlling bone homeostasis by regulating the function of both osteoblasts and osteoclasts. In addition, accumulating evidence demonstrates that osteocyte function is altered in several skeletal disorders, and targeting osteocytes and their derived factors improves skeletal health. Despite the remarkable progress in our understanding of osteocyte biology, there has been a paucity of information regarding the role of osteocytes in the progression of cancer in bone. Exciting, recent discoveries suggest that tumor cells communicate with osteocytes to generate a microenvironment that supports the growth and survival of cancer cells and stimulates bone destruction. This review features these novel findings and discussions regarding the impact of chemotherapy on osteocyte function and the potential of targeting osteocytes for the treatment of cancer in bone. © 2019 The Authors. JBMR Plus published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.